PENERAPAN PRINSIP SYARIAH PADA HOMESTAY SYARIAH - Amelia, Rika Nur; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The development of business in the hospitality industry attracted a lot of public attention. One of them is a hotel that adheres to the principle of Shariah. Hotels are usually used to carry out activities that lead to negative actions, so a lot of inclined views are directed at him. Because of this situation, some hotel businessmen are thinking and trying to create new innovations that are in line with the norms and rules of society and in accordance with the Islamic Shariah. This study focuses on how the principle of Shariah is applied to the Yariah homestay. The method used is using the library method. The results of the research show that the application of the principle of Shariah in its operations, both in the manufacture of goods, services, and management. The principles of Shariah are also shown in the hotel policy and general rules. This policy is derived from the services and products sold. Starting from choosing guests, chooses things that match the Shariah, and ensures that food and drink are halal. With the existing policy, if a Shariah hotel has a sharia-compatible policy, bad behavior like drunkenness, prostitution, eating illegal food, and behaviors that lead to impunity will be greatly reduced and will not even happen again.